An international circumpolar compilation of macronutrient concentrations in Antarctic land-fast sea ice: science highlights and open access data - Henley, Sian S.F.; Cozzi, Stefano; Fripiat, François; Lannuzel, Delphine; Nomura, Daïki; Thomas, David D.N.; Meiners, Klaus Martin; Vancoppenolle, Martin; Arrigo, Kevin K.R.; Stefels, Jacqueline; Van Leeuwe, Maria M.A.; Moreau, Sébastien; et al. (2023)
info:eu-repo/semantics/nonPublished